happy with solution rate this
If you would like to know the solution to the equation (x - 2) * (x + 5) = 18, you can calculate this using the following steps:
(x - 2) * (x + 5<span>) = 18
</span>x^2 + 5x - 2x - 10 = 18
x^2 + 3x - 28 = 0
(x + 7) * (x - 4) = 0
1. x = - 7
2. x = 4
The correct result would be x = - 7.
Answer:
1.07m
Step-by-step explanation:
the first step is to convert inches to cm
1in =2.54cm
(42.4in/1in x2.54cm)
42.4in = 107.69cm
then convert cm to m
1cm =0.01m
(107.69cm/1cm x 0.01m)
107.69cm =1.0769m
~1.07m
Answer:
D
Step-by-step explanation:
-2x+8.1y
+9x-5.3y
________
get the answer 7x+2.8y
Answer:
392 ft²
Step-by-step explanation:
Break this area into two parts, that is, into two trapezoids. The first trapezoid, on the left, has length 8 ft and average length (30 ft + 27 ft)/2, so its area is (8 ft)(28.5 ft) = 228 ft ².
The second trapezoid has width 8 ft and average length (19 + 22)/2 ft, or 8 ft by 20.5 ft). The area of this part is 164 ft².
Thus, the total area is 164 ft² + 228 ft², or 392 ft²